PENGARUH PEMANFAATAN PLATFORM MERDEKA MENGAJAR TERHADAP KEMAMPUAN MENGAJAR GURU SD DALAM IMPLEMENTASI KURIKULUM MERDEKA - Nuraeni, Vera; Widia Nur Jannah; Aiman Faiz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teachers have an important role in the learning process, effective learning activities require a comprehensive education system that is structured in the curriculum. The government provides the Independent Teaching Platform (PMM) as a means of teaching activities in implementing the independent curriculum. This research aims to find out how high the utilization of the Merdeka Mengajar Platform is for elementary school teachers in Arjawinangun District, Cirebon Regency. The research method used is quantitative research with a survey research design. The population of this research is all elementary schools in Arjawinangun District, totaling 325 teachers. The sample was selected randomly using probability sampling with a sample size of 100 teachers. Data collection techniques using questionnaires and documentation. The results of this research state that the level of utilization of the Merdeka Mengajar Platform (PMM) by elementary school teachers in Arjawinangun District is quite high and varied. Increased use of these platforms can be achieved through better technological support, more intensive training, and encouragement from school administration.